# (5x+4)(5x+4)=81

## Simple and best practice solution for (5x+4)(5x+4)=81 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (5x+4)(5x+4)=81 equation:

Simplifying
(5x + 4)(5x + 4) = 81
Reorder the terms:
(4 + 5x)(5x + 4) = 81
Reorder the terms:
(4 + 5x)(4 + 5x) = 81
Multiply (4 + 5x) * (4 + 5x)
(4(4 + 5x) + 5x * (4 + 5x)) = 81
((4 * 4 + 5x * 4) + 5x * (4 + 5x)) = 81
((16 + 20x) + 5x * (4 + 5x)) = 81
(16 + 20x + (4 * 5x + 5x * 5x)) = 81
(16 + 20x + (20x + 25x2)) = 81
Combine like terms: 20x + 20x = 40x
(16 + 40x + 25x2) = 81
Solving
16 + 40x + 25x2 = 81
Solving for variable 'x'.
Reorder the terms:
16 + -81 + 40x + 25x2 = 81 + -81
Combine like terms: 16 + -81 = -65
-65 + 40x + 25x2 = 81 + -81
Combine like terms: 81 + -81 = 0
-65 + 40x + 25x2 = 0
Factor out the Greatest Common Factor (GCF), '5'.
5(-13 + 8x + 5x2) = 0
Factor a trinomial.
5((-13 + -5x)(1 + -1x)) = 0
Ignore the factor 5.
Subproblem 1Set the factor '(-13 + -5x)' equal to zero and attempt to solve:
Simplifying
-13 + -5x = 0
Solving
-13 + -5x = 0
Move all terms containing x to the left, all other terms to the right.
Add '13' to each side of the equation.
-13 + 13 + -5x = 0 + 13
Combine like terms: -13 + 13 = 0
0 + -5x = 0 + 13
-5x = 0 + 13
Combine like terms: 0 + 13 = 13
-5x = 13
Divide each side by '-5'.
x = -2.6
Simplifying
x = -2.6
Subproblem 2Set the factor '(1 + -1x)' equal to zero and attempt to solve:
Simplifying
1 + -1x = 0
Solving
1 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + -1x = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -1x = 0 + -1
-1x = 0 + -1
Combine like terms: 0 + -1 = -1
-1x = -1
Divide each side by '-1'.
x = 1
Simplifying
x = 1Solutionx = {-2.6, 1}`